Medical Informatics Training at Columbia University and the Columbia-Presbyterian Medical Center - Cimino, J. J.; Allen, B. A.; Clayton, P. D. (Yearbook of Medical Informatics, 1995)
The Department of Medical Informatics at Columbia University College of Physicians and Surgeons consists of a faculty of 17 full-and part-time faculty. The Department faculty collaborate with the Department of Computer Science and several clinical departments of the medical center. We offer courses in medical informatics, formal degrees (M.A., M.Phil. and Ph.D.) and a postdoctoral training program. In addition to academic offerings, the close affiliation with the Columbia-Presbyterian Medical Center and the primary responsibilities for clinical information systems offers trainees unique opportunities to work with and develop real-world applications. Faculty research programs include work on the Integrated Advanced Information Management System (IAIMS), Unified Medical Language System (UMLS), High-Perfor-mance Computing and Communications (HPCC), Electronic Medical Records, automated decision support and technology transfer through the Center for Advanced Technology.
Keywords: Medical Informatics; Education; Training; Training Program; Graduate Program